Evaluasi Jamur Antagonis dalam Menghambat Pertumbuhan Rigidoporus microporus Penyebab Penyakit Jamur Akar Putih pada Tanaman Karet - Widi Amaria; Rita Harni; Samsudin Samsudin (Jurnal Tanaman Industri dan Penyegar, 2015)
Rigidoporus microporus is a pathogen causing white root disease in rubber plants, which is very difficult to control. The use of antagonistic fungi is expected to control this pathogen because it has the inhibitory ability through the competition, antibiosis or parasitism mechanisms. The objective of this research was to evaluate ten antagonistic fungi in inhibiting the growth of R. microporus in vitro. The research was conducted from January to April 2013, in the Laboratory of Plant Protection, Indonesian Industrial Beverages Crop Research Institute (IIBCRI) Sukabumi. The research consisted of: (1) the growth rate of colony, (2) inhibition, (3) secondary metabolites, and (3) antagonistic mechanism. Each test using a completely randomized design. The antagonist fungi used are: Trichoderma virens, T. hamatum,  T. amazonicum, Eupenicillium javanicum, Penicillium simplicissimum, P. citrinum, P. pinophilum, Paecilomyces lilacinus, Aspergillus fijiensis, and Hypocrea atroviridis (=T. atroviride), in which each of these fungi repeated 3 times. The results showed that the Trichoderma genus have inhibitory capability against R. microporus stronger than the others. Four genus of Trichoderma fungi have better competition mechanism against R. microporus compared to Penicillium, Eupenicillium, Paecilomyces, and Aspergillus. In addition, T. virens and H. atroviridis also have parasitism ability, while P. lilacinus and E. javanicum have antibiosis mechanism against R. microporus. The antagonistic fungi which were most potential to be developed as a biological control for white root disease, i.e.: T. virens, T. hamatum, and H. atroviridis.